1998
DOI: 10.1046/j.1365-2362.1998.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of relationship between the PlA1/PlA2 polymorphism of platelet glycoprotein IIIa and premature myocardial infarction

Abstract: These results suggest that the P1A2 polymorphism of the platelet glycoprotein IIIa does not contribute to the genetic susceptibility to premature myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Increased PIA2-prevalence in CAD and in patients after myocardial infarction was reported [31,32,33,34,35]. In a prospective nested case control trial within the Physician's Health Study no association was found of the PIA2-prevalence with any thrombotic endpoint at all and this was confirmed by the ECTIM and ARIC studies and by some smaller studies [36,37,38,39,40]. Others seem to resolve these striking differences by their suggestion that PIA2-prevalence does not act as a risk factor per se, but strongly determines the thrombogenic reactivity of the circulating platelets [32].…”
Section: Discussionmentioning
confidence: 88%
“…Increased PIA2-prevalence in CAD and in patients after myocardial infarction was reported [31,32,33,34,35]. In a prospective nested case control trial within the Physician's Health Study no association was found of the PIA2-prevalence with any thrombotic endpoint at all and this was confirmed by the ECTIM and ARIC studies and by some smaller studies [36,37,38,39,40]. Others seem to resolve these striking differences by their suggestion that PIA2-prevalence does not act as a risk factor per se, but strongly determines the thrombogenic reactivity of the circulating platelets [32].…”
Section: Discussionmentioning
confidence: 88%
“…Further subgroup analysis based on comparison of the PlA1/A1 versus PlA2/A2 genotype failed to show a significant association ( n  = 23,836; OR 1.023, 95% CI 0.877–1.192; p = 0.774) [70]–[72], [81], [82], [86][91], [95], [98][100], [102]–[104], [106]–[108], [111][114], [116], [117], [120], [122], [124], [128] (Figure 3); however, within this analysis, the number of subjects with the PlA2/A2 genotype was small, consisting of 333 cases and 1,504 controls.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of these studies revealed an association between carriage of the PlA2 allele and MI that was stronger than that seen in the primary analysis ( n  = 18,349; OR 1.131, 95% CI 1.036–1.234; p = 0.006) [82], [84], [86], [87], [90], [101], [104], [107], [111], [117], [119]–[122], [124], [125].…”
Section: Resultsmentioning
confidence: 99%
“…An association between the presence of the HPA‐1b polymorphism and coronary thrombosis was first reported by Weiss et al (1996). In the numerous epidemiological studies that followed, this association was both supported (Carter et al , 1997; Walter et al , 1997; Abbate et al , 1998; Garcia‐Ribes et al , 1998; Gardemann et al , 1998; Pastinen et al , 1998; Zotz et al , 1998; Kastrati et al , 1999; Zotz et al , 2000) and challenged (Hato et al , 1997; Herrmann et al , 1997; Ridker et al , 1997; Samani & Lodwick, 1997; Durante‐Mangoni et al , 1998; Scaglione et al , 1998; Sperr et al , 1998; Cenarro et al , 1999; Kekomaki et al , 1999; Laule et al , 1999).…”
mentioning
confidence: 95%